Does the eight-factor “power to live” in disaster exist since childhood? - Matsuzaki, Yutaka; Ishibashi, Ryo; Yasuda, Mari; Tanabe-Ishibashi, Azumi; Honda, Akio; Abe, Tsuneyuki; Sugiura, Motoaki (Frontiers in Public Health, 2022)
Studies on the survivors of the 2011 Great East Japan earthquake and tsunami have revealed eight factors, called power to live, which are closely related to resilience and effective coping after intense and prolonged stress. However, whether the eight factors, which were examined in adults, are applicable to children is unclear. The purpose of this study is to evaluate whether the eight-factor structure of power to live was present since late childhood. A 34-item power to live questionnaire was filled by middle- to upper-grade elementary (n = 378) and junior high school students (n = 456). Moreover, because elementary school students may lack introspective ability, their power to live was evaluated through a parental assessment (n = 358). Additionally, we examined the relationship between each power to live factor and questions regarding disaster prevention awareness among 25 elementary school students. The results from confirmatory factor analysis for factor structure revealed generally acceptable fit indices. The reports from elementary school students and their parents significantly positively correlated with each power to live factor. Although reliability indices for factors such as stubbornness, etiquette, self-transcendence, and active well-being were not good for elementary school students, the reliability indices for all factors, excluding stubbornness, increased in junior high school students. Moreover, we identified a correlation between problem-solving, altruism, and emotional regulation and questionnaire items regarding awareness of disaster prevention in elementary school students. Our results suggest that although factors common to adults, such as leadership, problem-solving, altruism, and emotional regulation, were identified at the elementary school stage, some factors, such as stubbornness, are in the process of being formed. Future studies should examine the developmental changes assumed to underlie these factors and their relationship to experience and neurodevelopmental basis.